The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1001/jamadermatol.2022.5437
|View full text |Cite
|
Sign up to set email alerts
|

Association of All-Cause and Cause-Specific Mortality Risks With Pyoderma Gangrenosum

Abstract: ImportancePyoderma gangrenosum (PG) is a rare neutrophilic dermatosis. Few studies have evaluated the mortality outcomes of patients with PG.ObjectiveTo investigate all-cause and cause-specific mortality in patients with PG.Design, Setting, and ParticipantsThis retrospective population-based cohort study used data from the National Health Insurance Service database of Korea and the National Death Registry of Korea from patients with incident PG (≥3 documented visits with an International Statistical Classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The addition of negative pressure wound therapy, such as VAC dressing, can help accelerate wound closure and healing [ 15 ]. PG has been associated with a higher mortality risk when compared to the general population, and the prognosis can be improved with a multidisciplinary approach [ 16 ]. Although our patient lost follow-up and did not undertake treatment at our center, wound coverage could have been subsequently achieved using a skin graft and a muscle flap if required, with excellent outcomes over subsequent follow-ups [ 4 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of negative pressure wound therapy, such as VAC dressing, can help accelerate wound closure and healing [ 15 ]. PG has been associated with a higher mortality risk when compared to the general population, and the prognosis can be improved with a multidisciplinary approach [ 16 ]. Although our patient lost follow-up and did not undertake treatment at our center, wound coverage could have been subsequently achieved using a skin graft and a muscle flap if required, with excellent outcomes over subsequent follow-ups [ 4 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the causes of this increase remain unclear, the mortality risk for PG patients is estimated to be three times higher than the general population [1]. A recent population-based cohort study by Lee et al [2] supported that PG patients have an elevated all-cause mortality risk. PG patients included in this study were shown to have a higher mortality risk from a multitude of conditions including infection, hematological disorders, neoplasm, and respiratory disease as compared to controls.…”
Section: Introductionmentioning
confidence: 99%